Novel compound heterozygous WDR35 variants in a Chinese patient associated with cranioectodermal dysplasia and ectopic testis: a case report and review of the literature - Lijie Li; Cuihua Liu; Ming Tian; Guangbo Li; Jitong Li (BMC, 2023)
Abstract Background WDR35 variants are known to cause a rare autosomal recessive disorder-Cranioectodermal dysplasia (CED). The CED patients are commonly present with facial dysmorphisms (frontal bossing and low-set ears), sagittal craniosynostosis, growth retardation, dolichocephaly, skeletal deformities (brachydactyly, terminal hypoplasia of the fingers and narrow thorax), ectodermal abnormalities (sparse hair, and finger/toe nail dysplasia), nephronophthisis, retinal dystrophy and hepatic fibrosis. Diagnosis of CED can be difficult because it presents with high genetic heterogeneity. However, our understanding of the phenotype of CED caused by WDR35 variants could be more explicit, and the correlation between genotype and phenotype needs further improvement. Case presentation We report a case of the first Chinses patient of CED caused by WDR35 variants, a 3-year-and-3-month-old patient, who was admitted to our hospital with frontal bossing, growth retardation, low set ears, dolichocephaly, sparse hair, and small limbs, abnormal renal function, and moderate anemia. The child showed a novel phenotype of the ectopic testis except for presenting typical CED characteristics, and he was identified with novel compound heterozygous WDR35 variants (c.2590 C > T, p.Gln864* and c.2408_2416del, p.Asn803_Ala805del; NM_001006657). He was given iron succinate and erythropoietin to improve anemia and to inhibit repeated metabolic acidosis and hyperkalemia through acid correction, diuretic, and potassium-lowering treatments. The parents refused to accept renal replacement therapy for their child and were discharged voluntarily. Conclusions This is the first reported case of the WDR35 variants that can lead to CED and ectopic testis, which is also the first Chinese patient associated with WDR35 variants. This study expands our understanding of genotype-phenotype association in patients with WDR35 variants and provides genetic counseling for prevention and intervention in this genetic disorder. Neonatal carriers should be followed up for kidney and CED-related diseases to detect warning signs.